Analisis Penerapan Value Engineering (VE) pada Proyek Konstruksi Menurut Persepsi Owner - Febriyanto, Andreas; Priyambodo, Bambang; Naibaho, Pio Ranap Tua; Sembiring, Kristina (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2026)
The implementation of VE in the construction sector is an approach carried out systematically by a team from many disciplines that focuses on value and function. The implementation of VE in construction projects has the potential for significant savings from the project budget. In the construction world, project owners are often faced with various constraints such as budget constraints, increasing material costs, and the need for time efficiency. VE offers a solution to overcome these constraints with a functional analysis-based approach that aims to increase value by reducing unnecessary costs without reducing the quality of the final product. The implementation of VE carried out in construction projects, the techniques and alternatives used vary, this is due to the approach used, cultural conditions, and different procurement systems. The purpose of this study is to identify VE practices in Indonesia, examine the success factors in these practices, knowledge and experience of VE, and the constraints often faced in VE practices. The research method was carried out by distributing questionnaires to respondents who had knowledge of VE. The data obtained from the questionnaire were analyzed using descriptive analysis. The results of the analysis show that the implementation of VE in Indonesia is carried out on projects that are being proposed and on projects that are underway, the knowledge and experience of construction actors are the main success factors, construction actors have sufficient knowledge about VE, and the lack of knowledge about VE is the main obstacle in the implementation of VE in Indonesia.